B chromosomes: from cytogenetics to systems biology - Valente, Guilherme T. [UNESP] (2017)
Though hundreds to thousands of reports have described the distribution of B chromosomes among diverse eukaryote groups, a comprehensive theory of their biological role has not yet clearly emerged. B chromosomes are classically understood as a sea of repetitive DNA sequences that are poor in genes and are maintained by a parasitic-drive mechanism during cell division. Recent developments in high-throughput DNA/RNA analyses have increased the resolution of B chromosome biology beyond those of classical and molecular cytogenetic methods; B chromosomes contain many transcriptionally active sequences, including genes, and can modulate the activity of autosomal genes. Furthermore, the most recent knowledge obtained from omics analyses, which is associated with a systemic view, has demonstrated that B chromosomes can influence cell biology in a complex way, possibly favoring their own maintenance and perpetuation.